Answer:
[tex]\displaystyle y-1=\frac{1}{3}(x+3)[/tex]
Step-by-step explanation:
Equation of a Line
The equation of a line passing through points (x1,y1) and (x2,y2) can be found as follows:
[tex]\displaystyle y-y_1=\frac{y_2-y_1}{x_2-x_1}(x-x_1)[/tex]
The table shows the relation between x and y. It contains the following points
(-3,1), (6,4), (12,6), (30,12).
Taking the two first points, we find the equation of the line:
[tex]\displaystyle y-1=\frac{4-1}{6+3}(x+3)[/tex]
[tex]\displaystyle y-1=\frac{3}{9}(x+3)[/tex]
Simplifying:
[tex]\displaystyle y-1=\frac{1}{3}(x+3)[/tex]
To ensure the rest of the points belong to the line, we test them:
For the point (12,6):
[tex]\displaystyle 6-1=\frac{1}{3}(12+3)[/tex]
[tex]\displaystyle 5=\frac{1}{3}(15)[/tex]
5=5
Since equality is true, the point belongs to the line.
For the point (30,12):
[tex]\displaystyle 12-1=\frac{1}{3}(30+3)[/tex]
[tex]\displaystyle 11=\frac{1}{3}(33)[/tex]
11=11
Since equality is true, the point belongs to the line.
Thus, the equation of the line is:
[tex]\mathbf{\displaystyle y-1=\frac{1}{3}(x+3)}[/tex]